Identifikasi Faktor Penyebab Keterlambatan Pengambilan Logistik Non-Medis Menggunakan Diagram Fishbone di Rumah Sakit Muhammadiyah Lamongan - Mila Lutfiyatun An’nisa; Nuryati; Faizatul Ummah (Rena Cipta Mandiri, 2026)
Delays in non-medical logistics retrieval are a problem that can reduce distribution effectiveness in hospitals. This study aims to identify the factors causing delays in non-medical logistics retrieval and to propose improvement efforts. The research used a descriptive qualitative method with an observational approach through observation, interviews, and documentation at the General Logistics Unit of Muhammadiyah Hospital Lamongan from February to March 2026. Data were analyzed using a fishbone diagram to identify root causes. The results showed that delays were influenced by factors related to human resources, methods, materials, systems, and environment, including high workload, absence of retrieval time limits, low urgency of items, suboptimal system utilization, and ineffective inter-unit communication. These conditions lead to stock accumulation in the warehouse and reduced distribution efficiency. Therefore, it is necessary to establish SOP for retrieval time limits, implement reminder systems, and improve coordination and communication between units.